Humidtropics Evaluation Report - Rwampororo, R.K., Negra, C., Kueneman, E. (International Institute of Tropical Agriculture, 2015)
The evaluation is one of the five CRP commissioned evaluations requested by the CGIAR Fund Council, to assist and inform he planning and approval process for Phase II of the CRPs. To assist CRPs in this effort, IEA provided quality assurance advice and support, as well as quality validation and review of processes and outputs.